The Essential Oil from Oliveria decumbens Vent. (Apiaceae) as Inhibitor of Breast Cancer Cell (MCF-7) Growth - Mandana Shariatzadeh; Akbar Karami; Ali Moghadam; Mahbobeh Lotfi; Filippo Maggi; Esmaeil Ebrahimie (MDPI AG, 2022)
Oliveria decumbens Vent. is an aromatic and medicinal plant traditionally used in Iran for the treatment of infections, gastrointestinal diseases, cancer, and inflammation. This research was aimed at investigating the pharmacological potential of O. decumbens essential oil (OEO) and its main compounds, focusing on OEO's cytotoxic effects on MCF-7 breast cancer cells. OEO was obtained by hydro-distillation, and the chemical constituents were identified using GC-MS. Thymol, carvacrol, γ-terpinene, and p-cymene were the main OEO constituents. When MCF-7 cells were treated with OEO, the expressions of genes related to apoptosis (BIM and Bcl-2), tumor suppression (PTEN), and cell growth inhibition (AURKA), were evaluated using real-time PCR. Moreover, molecular docking was used for studying in silico the interaction of OEO principal compounds with PTEN and AURKA. The expression of AURKA was significantly reduced since the OEO treatment enhanced the expression of PTEN. Through in silico molecular docking, it was revealed that thymol, carvacrol, p-cymene, and γ-terpinene can activate PTEN and thus inhibit AURKA. Additionally, the DNA fragmentation assay, acridine orange/ethidium bromide (AO/EB) double-staining assay, and real-time PCR highlighted the fact that the OEO treatment could activate apoptosis and inhibit cell proliferation. Therefore, OEO is a viable candidate to be employed in the pharmaceutical industry, specifically as a possible agent for cancer therapy.